Application Of A Communicative Approach In Learning Arabic To Improve Students' Skills In Speaking Arabic - Najib Halim, Fahmi; Masri'ah, Masri'ah; Nurwahidah, Nena (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The purpose of this study was to determine the speaking skills of class VIII students before applying a communicative approach to Majalengka Arabic learning. To find out the process of applying a communicative approach in learning Arabic. To determine the speaking skills of class VIII students after applying a communicative approach to learning Arabic. The method used in this study is a quasi-experimental design with a quantitative approach. And data collection in this study is by way of observation, interviews, and tests.The results of this study are evidenced by the comparison of data in the control class that does not use a communicative approach with the average score of 68.23 students, the lowest score is 40, and the highest score is 92. The data scores in the experimental class using the communicative approach. with the acquisition of an average student score of 78.87, the lowest score of 66, and the highest score of 93. Therefore, it can be concluded that the application of a communicative approach in learning Arabic to improve students' ability to speak Arabic is declared successful with the existence of free test and post test and proved by the formula t = 005 > 000 which means Ha is rejected and Ho is accepted.